Analisis Kinerja Ruas Jalan Kenjeran, Simpang Apill (Jl. Kenjeran - Jl. Tambak Rejo), dan Simpang (Jl. Kenjeran - Jl. Sidotopo Wetan) Akibat Tundaan Perlintasan Sebidang Jpl 3 Sidotopo Surabaya - Bilal Zamzami; Ratih Sekartadji; Kurnia Hadi Putra; Theresia Maria (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Traffic congestion caused by railway level crossings is a serious urban problem, especially on Kenjeran Road affected by the closure of the JPL 3 Sidotopo gate in Surabaya. This closure creates total blocked time, triggering long queues that spill back to adjacent intersections. This study aims to evaluate the existing traffic performance of Kenjeran Road, the signalized intersection (Kenjeran–Tambak Rejo), and the unsignalized intersection (Kenjeran–Sidotopo Wetan) using the 2023 Indonesian Road Capacity Guidelines (PKJI), and to propose an alternative solution in the form of a flyover. Primary data were collected through field surveys during three peak periods on weekdays and weekends, covering traffic volume, road geometry, and gate closure duration. Performance analysis included calculation of capacity, degree of saturation, queue length, and delay, supported by visual simulation using PTV Vissim 22. Results show that existing conditions are highly critical, with a road degree of saturation reaching 0.98, a level crossing delay of 56.14 sec/pcu, and a signalized intersection degree of saturation of 1.34, indicating oversaturated conditions. After implementing a flyover that separates straight-through light and heavy vehicle flows, significant improvements were achieved: the underpass road degree of saturation dropped to 0.63, the signalized intersection to 0.50, the unsignalized intersection to 0.41, and crossing delay decreased to 27.24 sec/pcu. These findings confirm that vertical separation of traffic flows effectively restores network service levels.